Investigation of low dielectric constant (k) films for deep sub-micron CMOS application. - Cheon'g, Kuan Yew; Hussain, Luay Bakir (Universiti Sains Malaysia, 2007)
Silica (Si02) thin film on Si with low dielectric constant (k) properties has been systematically prepared and investigated. Two types of this low-k material have been deposited on Si via sol-gel spin-on coating.